Association between basic psychological needs of the self-determination theory and perception of group cohesion among high-performance futsal athletes - José Roberto Andrade do Nascimento Junior; Carla Thamires Laranjeira Granja; Adson Alves da Silva; Leonardo de Sousa Fortes; Marina Pereira Gonçalves; Daniel Vicentini de Oliveira; Lenamar Fiorese (Universidade Federal de Santa Catarina, 2019)
This study aims to investigate the association between satisfaction of basic psychological needs of the self-determination theory, and perception of group cohesion among male futsal athletes. In total, 301 athletes from 20 teams, participants of the Brazilian Futsal League participated in this study. The instruments used were the Basic Needs Satisfaction in Sport Scale (BNSSS) and the Group Environment Questionnaire (GEQ). Data analysis was conducted through the Structural Equation Modeling. Results revealed that the satisfaction of basic psychological needs presented significant association with group cohesion, explaining 28% of Task Cohesion and 63% of Social Cohesion variances. The satisfaction of the three basic psychological needs is associated with Task Cohesion, while only the satisfaction of basic psychological needs of Relatedness and Competence was associated with Social Cohesion. It was concluded that, in the context of high-performance futsal, the satisfaction of athletes with their basic psychological needs is associated with involvement with team goals and the likelihood of making friends within the group.